TECHNOLOGY PROVIDING SECONDARY PROTECTION METAL STRUCTURES AGAINST CORROSION UNDER AGGRESSIVE IMPACT OF METALLURGICAL PRODUCTION (Collection of scientific works «Modern structures of metal and wood», 2021)
Research is aimed at the formation and development of innovative developments to increase the metal structures corrosion protection, as an important means of ensuring the quality and safety industrial  facilities.  The  method  determining  the  corrosion  destruction  signs,  the  procedure  of monitoring and carrying out measures to diagnose the technical condition of lattice metal structures according to the level of corrosion hazard were adopted. The nomenclature indicators and control methods (conformity assessment) of determining parameters primary and secondary protection metal designs against corrosion is established. During this study, the lattice structures operational condition loader crane’s girder structure was considered. It is revealed that operation of the crane is carried out in difficult production conditions operating environment’s aggressive influence in combination with considerable dynamic loadings working operations loading technological process, unloading, sorting (averaging)  of  ore  yard’s  charge  of  blast  furnace  shop.  Based  on  the  study  structures  corrosion condition and operating conditions, measures have been developed to increase the durability ore-grab crane of the reloader. Based on the analysis of the principles of the ISO 9001 process approach, the development and implementation design solutions to extend the structures service life in aggressive environments of metallurgical production. It is proved that the procedure of making constructive and technological decisions, performance works on increase corrosion resistance promotes maintenance conditions of resource saving and technological safety industrial constructions. The principles process is  offered  to  develop  and  implement  design  measures  to  extend  the  service  life  of  structures  in aggressive  environments  metallurgical  production  are  proposed.  Constructive  and  technological measures to ensure durability in accordance with the requirements of the building structure corrosion risk have been developed, which are determined by the critical indicators metal structures protection in the conditions corrosion influences within their limit values.